Lactobacillus Suppresses Tumorigenesis of Oropharyngeal Cancer via Enhancing Anti-Tumor Immune Response - Wang, Ke-Ke; He, Kai-Yue; Yang, Jing-Yu; Liu, Meng-Jie; Guo, Jin-Rong; Liang, Ji-Yong; Wang, Jin-Hua; Xu, Zhi-Xiang; Jian, Yong-Ping (Frontiers in Cell and Developmental Biology, 2022)
Deficiency in T cell-mediated adaptive immunity, such as low CD8+ T cell infiltration, inhibits the immune surveillance, promotes malignant transformation, and facilitates tumor growth. Microbiota dysbiosis diminishes the immune system and contributes to the occurrence of cancer. However, the impact of oral dysbiosis on the occurrence and molecular mechanisms of oropharyngeal cancer (OPC) remains largely unknown. In the current study, we used 4NQO to mimic tobacco-related carcinogenesis to generate a murine OPC model and determine the role of microbiota changes in OPC tumorigenesis. Our results showed that the oral flora composition of mice was deregulated during the tumorigenesis of OPC. The abundance of Streptococcus, Veillonella, Muribacter, Rodentibacter, and Gemella was increased, whereas the dominant genus Lactobacillus was gradually decreased with disease progression. We further demonstrated that infiltration of CD8+ T lymphocytes was markedly reduced due to the reduction of Lactobacillus. Supplementation of Lactobacillus increased the infiltration of CD8+ T cells, promoted the expression of IFN-γ and granzyme B, and lessened the OPC progression. Analyzing the metabolites of the Lactobacillus, we demonstrated that Lactobacillus enhanced the anti-tumor immune response by producing acetate in OPC development. Administration of acetate to mice could increase the expression of IFN-γ and IFN-γ-inducible chemokines in tumor tissues by activating GPR43 to promote the infiltration of CD8+ T lymphocytes and substantially delay the development of OPC. Together, our data suggest that dysbiosis of oral microbiota promotes the tumorigenesis of OPC through downregulation of cytotoxic T lymphocytes. Lactobacillus and its metabolite acetate improve the tumor microenvironment, which could be applied in the treatment of OPC.